PENERAPAN TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA INFORMASI DAN SIMULASI TES PRAKTIK PADA PEMBUATAN SIM C BERBASIS ANDROID - Fadlan Sani Mubarok; Novian Adi Prasetyo; Ariq Cahya Wardhana (UNIVERSITAS PELITA HARAPAN, 2023)
The rapid development of Science and Technology (IPTEK) makes the number of motorcycle vehicles increase every year. It was recorded that in the last 5 years from 2015 – 2019 there was an increase in the number of motorcycles by 24.12 million. With this, the riders also experience an increase. So with this increase, it must be balanced with SIM C ownership so that motorists can understand traffic regulations and are skilled at driving motorized vehicles. On the other hand, Information and Telecommunications Technology is progressing rapidly. One of the technologies that are currently busy is Augmented Reality. Therefore, this study makes an application that aims to provide information and Simulations regarding practical tests on SIM C making by utilizing Augmented Reality technology will be much easier. Making this application using Unity and Vuforia by using the Marker Based Tracking method. This study uses the MDLC (Multimedia Development Life Cycle) method as a Multimedia application development. The final results will be tested using the system performance test and user satisfaction using the System Usibility Testing (SUS) method. In the SUS method, there are 10 questions with 5 answer options for each question, ranging from strongly disagree to strongly agree. The SUS questionnaire involves at least 10 system users.